Scientific Promotions - University of Baghdad model - Abd Al-Hadi, Maysoon Ali (Opción, 2019)
Academic advancement means the transfer of the academic staff member who hold’the academic title (assistant teacher, teacher, assistant professor, professor), whether he is teaching university, scientific research or scientific or technical consultation, who works in the office of the Ministry of Higher Education and Scientific Research or its institutions, To a higher scientific rank with a new scientific title after fulfilling the requirements and require- ments of this title in accordance with the law and these conditions set by the instructions of scientific promotion No. 167 of 2017, which are different conditions of the provisions contained in the provisions of the promotion of Scientific No. 36 of 1992 repealed, private Higher Education No. 25 of 2016 which upgrade fee mechanism for the campaign of scientific titles in universities, community colleges and institutes canceled so private universi- ties and colleges Law No. 13 of 1996.